Differential effects of acute cardiovascular exercise on explicit and implicit motor memory: the moderating effects of fitness level - Cristini, Jacopo; Kraft, V. S.; De las Heras, B.; Rodrigues, L.; Parwanta, Z.; Hermsdörfer, J.; Steib, Simon; Roig, M. (Neurobiology of learning and memory, 2023)
A single bout of cardiovascular exercise (CE) performed after practice can facilitate the consolidation of motor memory. However, the effect is variable and may be modulated by different factors such as the motor task’s or participant’s characteristics and level of awareness during encoding (implicit vs explicit learning). This study examines the effects of acute CE on the consolidation of motor sequences learned explicitly and implicitly, exploring the potential moderating effect of fitness level and awareness. Fifty-six healthy adults (24.1 ± 3.3 years, 32 female) were recruited. After practicing with either the implicit or explicit variant of the Serial Reaction Time Task (SRTT), participants either performed a bout of 16 min of vigorous CE or rested for the same amount of time. Consolidation was quantified as the change in SRTT performance from the end of practice to a 24 h retention test. Fitness level (V̇O2peak) was determined through a graded exercise test. Awareness (implicit vs explicit learning) was operationalized using a free recall test conducted immediately after retention. Our primary analysis indicated that CE had no statistically significant effects on consolidation, regardless of the SRTT’s variant utilized during practice. However, an exploratory analysis, classifying participants based on the level of awareness gained during motor practice, showed that CE negatively influenced consolidation in unfit participants who explicitly acquired the motor sequence. Our findings indicate that fitness level and awareness in sequence acquisition can modulate the interaction between CE and motor memory consolidation. These factors should be taken into account when assessing the effects of CE on motor memory.
Online verfügbar 21 October 2023, Version des Artikels 23 October 2023
Gesehen am 17.01.2024